Assessment and Management of Pain in Juvenile Idiopathic Arthritis - Jennifer N Stinson; Nadia JC Luca; Lindsay A Jibb (Pain Research and Management)
Juvenile idiopathic arthritis (JIA) is a common chronic childhood illness. Pain is the most common and distressing symptom of JIA. Pain has been found to negatively impact all aspects of functioning, including physical, social, emotional and role functions. Children with arthritis continue to experience clinically significant pain despite adequate doses of disease-modifying antirheumatic drugs and anti-inflammatory agents. The present article reviews the prevalence and nature of pain in JIA, the biopsychosocial factors that contribute to the pain experience, current approaches to assessing pain in this population, and ways of managing both acute and persistent pain using pharmacological, physical and psychological therapies. Finally, new approaches to delivering disease self-management treatment for youth with JIA using the Internet will be outlined.